2012
DOI: 10.1002/jctb.3848
|View full text |Cite
|
Sign up to set email alerts
|

Towards high resolution membrane‐based pharmaceutical separations

Abstract: BACKGROUND In this work the possibility of using membrane cascades to carry out difficult pharmaceutical separations was explored. The effect of configuration on process yield, time and cost was studied for a challenging industrial separation: the separation of an intermediate I (MW 221 g mol−1) from an impurity, ethylene bromide (MW 188 g mol−1). RESULTS All cascade configurations studied were capable of increasing the purity from a fairly low value, namely 26% to the 90% requirement. The results from the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…Membrane cascades offer potentially large gains in selectivity and they were developed, often on a purely theoretical basis [15][16][17] although partially experimental [18][19][20][21][22][23] and fully experimentally validated examples exist [4,12,[24][25][26][27]. Much of the published work extrapolates single-stage screening results to predict and analyse the performance of multiple stages.…”
Section: Control Of Membrane Cascades and Implementation Of Solvent Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane cascades offer potentially large gains in selectivity and they were developed, often on a purely theoretical basis [15][16][17] although partially experimental [18][19][20][21][22][23] and fully experimentally validated examples exist [4,12,[24][25][26][27]. Much of the published work extrapolates single-stage screening results to predict and analyse the performance of multiple stages.…”
Section: Control Of Membrane Cascades and Implementation Of Solvent Rmentioning
confidence: 99%
“…Whilst the predictive capability for two-or three-stage cascades may actually be sufficient to warrant the conclusions drawn, there are major obstacles to industrial implementation. Beside the diminishing economic benefit of introducing additional stages [18], process control is challenging with large cascades due to the step increase in complexity and the larger number of equipment needed. Whilst in many ways considered a temperature-flexible, pressure-driven analogue of distillation, a membrane cascade shares many of the same process control problems.…”
Section: Control Of Membrane Cascades and Implementation Of Solvent Rmentioning
confidence: 99%
“…These studies showed the feasibility of OSN technologies in different industries at laboratory scale with flat sheet membranes or with 1.8"x12" spiral-wound membrane modules. In the literature, only a few studies [Peshev et al, 2011;Vanneste et al, 2013;Sereewatthanawut et al, 2010] proposed mathematical models for prediction of the process performance. In these process models, the mass balance equations were derived based on the assumptions of well-mixed solutions in a feed tank and negligible time consumed for retentate circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafiltration and nanofiltration are the most frequently used membrane technologies for biotechnological and pharmaceutical purposes. Ultrafiltration is widely used for the separation and fractionation of proteins and other biological molecules and nanofiltration cascades have been implemented for pesticide removal, solvent exchange, solvent recovery, and separation and fractionation of pharmaceutical solutes …”
Section: Introductionmentioning
confidence: 99%